Hamman’s Syndrome Accompanied by Diabetic Ketoacidosis; a Case Report - Yamashita, Koya; Hongo, Takashi; Nojima, Tsuyoshi; Yumoto, Tetsuya; Nakao, Atsunori; Naito, Hiromichi (Archives of Academic Emergency Medicine, 2022)
Hamman’s syndrome is an uncommon clinical entity characterized by an idiopathic spontaneous pneumomediastinum as a result of a sudden increase in intra-alveolar pressure. It can be triggered by repeated vomiting or Kussmaul breathing associated with diabetic ketoacidosis (DKA). Substantially, careful attention to this particular condition is needed to avoid underdiagnosis and to provide optimal management. Herein, we report a case of an 18-year-old man complaining of chest discomfort and progressive weight loss, ultimately diagnosed with Hamman’s syndrome secondary to DKA. The patient’s symptoms disappeared after intravenous fluid and insulin administration, while his pneumomediastinum resolved following conservative treatment. Our report highlights the importance of recognition of the links between pneumomediastinum and DKA.